Wireless Infrared Communications with Edge Position Modulation for Mobile Devices - Lüftner, Thomas; Kröpl, Christian; Hagelauer, Richard; Huemer, Mario; Weigel, Robert; Hausner, Josef (IEEE Wireless Communications, 2003)
Driven by the Infrared Data Association, wireless infrared communication has become a very popular and widely used method for short-range data transmission between mobile devices like laptops, PDAs, and mobile phones. Especially in ad hoc connection applications, IrDA excels over radio-based solutions like Bluetooth or cable-based solutions like USB, due to the point-and-shoot characteristic of infrared communication. The quality and speed of infrared communications are mainly limited by the bandwidth of infrared transceivers. Therefore, it is important to use a modulation technique with high bandwidth efficiency, while simultaneously maintaining a low bit error rate and high power efficiency. Consequently, the IrDA has continuously improved the modulation techniques of its standards by introducing return to zero inverted (RZI) for the serial infrared (SIR) mode, 4-PPM for the fast infrared mode, and HHH(1,13) for the latest very fast infrared mode. This article presents a new modulation scheme called edge position modulation (EPM) with RLL coding, which offers increased bandwidth efficiency over the previous methods and attractive power efficiency. Since the novel modulation technique can be optimized to the characteristics of the wireless infrared channel, it also maintains low bit error rates.
elib2cris::1512001600,lueftner2003a
Keywords: infrared communication; IrDA; USB; Bluetooth; modulation techniques; HHH(1; 13); Edge Position Modulation; EPM; Run-Length-Limited Code; RLL(5; 12)